Factors influencing satisfaction on YouTube usage among students - Nazari, Nur Syahirah; Wok, Saodah (Communication Department, Faculty of Modern Languages, Universiti Putra Malaysia, 2018)
YouTube is one of the social networking sites using a video and it is very attractive among young generation especially the students. Therefore, this study aims to determine the relationship of among perception, attitude, behavior, impact and satisfaction on YouTube usage and to identify the best predictor for YouTube satisfaction. Uses and Gratification Theory is used to explain satisfaction on the YouTube usage among students. This study employs a quantitative research design using survey method with questionnaire as its research instrument for data collection. A total of 229 respondents were participated in the study. The results show that students have positive perception, attitude, behavior, impact and satisfaction on YouTube. There are positive relationships among the variables and the best predictor for satisfaction on YouTube usage is impact of YouTube on the students.